Tom Dawe Tape 5 - Memorial University of Newfoundland. Extension Service. Media Unit (Producer) (Memorial University Extension Service, 1983)
An interview with Tom Dawe in which he talks about his poetic style and the common themes in his poetry; he also describes his personal history and development, including the storytelling he heard as a young person. Original footage with some retakes.